KAJIAN MANAJEMEN RISIKO PADA PT PRO INTERTECH INDONESIA KOTA SORONG PROVINSI PAPUA BARAT - Mona Julike Latuhihin; Bambang Triyanto (INTAN Jurnal Penelitian Tambang, 2020)
In a mining company, of course, has a risk management system that aims to be able to identify any potential hazards that can occur around the mining and processing area and to make controls before a work accident occurs. One of the characteristics of the mining industry is that it is capital intensive, technology intensive and high risk, so it is necessary to identify and analyze risks for every job in the field, the method used in analyzing potential hazards and risk analysis is the Job Safety Analysis method which aims to identify and analyze each work steps and look for solutions or control methods if there is a potential hazard that can result in a work accident, one of the steps or efforts to protect workers in the field is to use personal protective equipment so that workers can be protected if at any time a work accident occurs in the field.